The network origins of the gains from trade - Maarten Bosker; Bastian Westbrock (Center for Economic Studies and ifo Institute (CESifo), 2019)
In this paper, we develop a network perspective on the welfare gains from trade in today's internationally fragmented supply chains. Towards this end, we study a Ricardian trade model featuring trade in final and intermediate products, and introduce a novel comparative statics approach to decompose the total welfare effects of an arbitrary trade cost shock into several meaningful, easily quantifiable, components. This approach uncovers a unique feature of supply chain trade: the gains from trade are not so much determined by a country's own access to the technologies and markets of its direct trading partners, but rather by its supply chain exposure to countries further up- and downstream in the global supply chain. We develop a set of simple statistics to measure each country's supply chain exposure, show how it predicts the gains from trade, and identify each country's key trade intermediaries, i.e., other nations that primarily leverage its supply chain exposure.
Keywords: F10; F11; 330; global supply chains; gains from trade; network diffusion; network exposure; trade intermediation